Antibacterial effect of centella asiatic ethanolic extract on staphylococcus aureus - Muhammad Afdhaluddin Hassan (2022)
Antibiotic treatments can result in multi-drug resistance in a variety of pathogens. To address this issue, an antibiotic alternative is required. Centella asiatica ethanolic extract was tested for antibacterial activity against Staphylococcus aureus. The study's goal is to determine the antibacterial effect of an ethanolic extract of C. asiatica against S. aureus at various concentrations. In this study, C. asiatica was found to have antibacterial activity by inhibiting the growth of S. aureus. Agar diffusion method with ethanolic C. asiatica extract was used to test the antimicrobial activity of the plant toward S. aureus. The results from this study show that there is zone produced on the Mueller Hinton Agar (MHA) for S. aureus. In conclusion, according to the findings of the study, using C. asiatica ethanolic extract as an antibacterial agent and alternative antibacterial for controlling S. aureus could be a new source of antibacterial agent. Keywords: Centella asiatica, Staphylococcus aureus, antibacterial activity